PERCEPTIONS OF MARGINALIZED PEOPLE ON BIRTH RATE CONTROL (International Conference on Social and Islamic Studies, 2021)
The government's efforts to control population growth can be seen from their support for relevant agencies to optimize birth rate control. Fertility is the main component of population growth is closely related to infant mortality, education levels, and the economy. In 2019, Indonesia's total fertility rate is still 2.2 per woman, above the target value of 2.1 per woman to create a prosperous family. The Covid-19 pandemic, which has forced changes in all areas of life, including the government's large-scale social restriction (LSSR) policy, has again triggered an explosion in the birth rate. It is further exacerbated by the decline in the use of Contraceptives. Contraceptive implants decreased from 81,062 to 51,536, injectables from 524,989 to 341,109, birth control pills from 251,619 to 146,767, condoms from 31,502 to 19,583, MOP (vasectomy) from 2,283 to 1,196, and MOW (tubectomies) from 13,571 to 8,093. Public knowledge of contraceptives and the choice of long-term contraceptive methods (LTCM) can stimulate the optimization of birth control. Therefore, this research focuses on looking at the perception of marginalized people in Makassar City on birth control. This study is an analytical survey with four knowledge indicators, namely understanding birth control, prosperous families, risk of early marriage, and long-term contraceptive methods. The survey results show that 95 people, 6% understand well about birth rate control, 97.8% are good for prosperous families, and 100% are good for long-term contraceptive methods. Statistical analysis test proves that understanding birth rate control, the  prosperous family, and long-term contraceptive method has a significant relationship with each p-value = 0.00 <0.05.